Optimising treatment system for kenaf (Hibiscus cannabinus) particleboard with fire retardants - Kamal, Izran; Ashaari, Zaidon; Beyer, Guenter; Abdul Malek, Abdul Rashid; Abood, Faizah; Sudin, Rahim (Forest Research Institute Malaysia, 2010)
Particleboard is widely used for panelling, partitioning and ceiling in buildings. The treatment of this material to improve fire performance is not an exception. A study was carried out to determine the fire performance of kenaf particleboard treated with phosphorous-based fire retardants. Kenaf core particles were first treated separately with 8 and 10% solutions of monoammonium phosphate (MAP), diammonium phosphate (DAP) and a mixture of boric acid, guanylurea phosphate and phosphoric acid (BP®) using hot and cold bath processes. The soaking time needed to achieve the standard dry salt retention, i.e. 50 kg m-3 was determined. Particleboards from these treated kenaf particles were fabricated and their fire performance evaluated. Using 8% treating solution, it took about 36, 21 and 48 min of immersing in cold bath to achieve the standard retention requirement for MAP, DAP and BP® respectively but for 10% concentration, the times were slightly shorter, i.e. 15, 20 and 35 min respectively. Among the three phosphorous formulations, BP® showed the best performance in improving the insulation and integrity of kenaf particleboard when exposed to fire. This is followed by MAP and DAP. BP®-treated board was the last to ignite compared with the other two boards.